ANALISIS PENGELOLAAN TENAGA KERJA INDONESIA (TKI) DI JAWA TIMUR - Eni Sri Rahayuningsih (MediaTrend, 2006)
This research is focuses on the existence "Overseas Contract Workers (OCWs)" that has relations to deportation versus foreign exchange. The research has the following goals : (1) To know and to analyze the influential factors on OCWs policies; (2) To know and to analyze the existence of migrant workers; (3) To know and to analyze government and private company management for migrant worker regarding deportation.This research is the case study with double approaches (qualitative and quantitative). The respondets are selected through purposive sampling with 150 respondets (117 respondets working at abroad and 33 respondets working at this country). Data collection through is done by observation, indepth interview and documentation technique. The respondet investigation is carried out by snowball technique. The research instruments used are check-list and questionnaire. Both qualitative and quantitative methods are used to analyze are logit model and equilibrium market supported by SCP analyze (structure - conduct - performance).The result indicates that : (1) The influential factors on OCWs decision are : wage factor and knowladge, because of risk probability in the overseas and their family. On other hand, age, education, information, push and pull factor has unreal influence. These conditions are generated from pressures lack of job oppurtunity and hope to prosperity; (2) The existence of OCWs (legal or illegal) are greatly influenced by supply and demand in the market labour. The implication is that OCWs has contributed foreign exchange. Because of the bargaining power OCWs is lower cause deportation; (3) Management of OCWs begins from : recruitment, training, departure and arrival. Government policy should focuses activity on handling the current conditions so that policy must be done, these return illegal OCWs into legal OCWs. Alternative model in the management of OCWs are : (a) reorganize the institution of OCWs, (b) to accommodate OCWs on horizontal integration in the form of association; (c) to manage the information become better than before.Based on the result of the research, it is suggested that : (1) The government must create job, while private institution (PJTKI) must change the role of management which not only profit orientation, but also becomes the protection for OCWs and their family; (2) In order to increase bargaining position, OCWs must do horizontal integration by establishing the organization.